Linguacultural Problem of the Literary Translation from Uzbek into English (On the Materials Of ‘Bygone Days’ by Abdullah Qodiri) (Eurasian Journal of Learning and Academic Teaching, 2023)
This article deals with the issues of interpretation and equivalency, particularly with social words, which display national traditions and conventions. Social terms ordinarily show less issues. In this article, incredible consideration is paid to the national-cultural specificity of interpretation of Uzbek classical writing into English. Translation from the mother tongue into a remote dialect must comply with phrased and elocution standards of the target dialect to such a degree that the thoughts, eagerly and truthful data contained within the unique discourse and the demeanor of the speaker to them are passed on in such a way that communication isn't disabled nor errors caused. Roman Abdulla Qadiri, “ Bygone days ” uncovers a wide run of widespread human subjects and issues. Subsequently, it is exceptionally troublesome to characterize it unambiguously